LINGUISTIC IDENTITY AND POWER IN MSME CODE-SWITCHING ADVERTISEMENTS: A CRITICAL DISCOURSE STUDY OF WEST SUMATERA - Edwar Kemal; Suhaida Omar (Jurnal Gramatika, 2025)
This research explores how Micro, Small, and Medium Enterprises (MSMEs) in West Sumatra employ code-switching in their advertising discourse to construct linguistic identity, express cultural belonging, and project entrepreneurial modernity. Using Fairclough’s Critical Discourse Analysis (CDA) as the analytical framework, this study examines linguistic features, forms of code-switching, and the underlying ideological meanings within promotional banners and billboards that combine English and Indonesian. The findings reveal that code-switching serves as more than a marketing strategy it functions as a socio-symbolic practice through which entrepreneurs negotiate between local authenticity and global aspirations. The frequent use of English, despite notable errors in diction, spelling, and syntax, underscores its symbolic power as a marker of prestige and progress in the post-pandemic economic landscape. However, these linguistic inaccuracies also indicate challenges in language proficiency and access to educational resources, exposing power asymmetries between local entrepreneurs and global linguistic norms. From a sociolinguistic standpoint, code-switching embodies both empowerment and vulnerability: it enables small businesses to gain visibility in global markets while simultaneously revealing structural inequalities in linguistic capital. The study concludes that language operates as a key site of negotiation where identity, economy, and ideology intersect. It recommends enhancing critical language awareness and multilingual marketing literacy in MSME training programs. Future research is encouraged to examine digital advertising discourses to understand how linguistic entrepreneurship evolves in online spaces. This study contributes to the growing body of literature on sociolinguistics, linguistic entrepreneurship, and the politics of language in Indonesia’s evolving marketplace.